LOCAL SHOE SELECTION DECISIONS WITH A DECISION SUPPORT SYSTEM USING THE SIMPLE ADDITIVE WEIGHTING METHOD - Tio Adi Kurniawan; Agus Iskandar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Shoes are a basic need that is very essential in everyday life. provides protection, comfort and adaptability to a variety of activities and environments. (Juliana iHutapea iet ial., i2018) However, when choosing shoes, the task can become quite complicated considering the many choices and factors that need to be considered. In Indonesia, there are many local shoe brands, each with its own characteristics and appeal. The diversity of shoe models available often creates confusion for buyers, who are looking for shoes that suit their needs and preferences. (Mario i& iLero, in.d.) To overcome this challenge, this research aims for the same. to develop a decision support system designed to provide assistance to buyers in choosing shoes. This research involves three main criteria, namely price, comfort, and quality, which are considered key factors in carrying out the decision-making process. purchasing shoes. By applying the Simple Additive Weighting (SAW) method (Apriani iet ial., i2020), this research attempts to produce weights for each criterion and provide a ranking of shoes that could be the right choice. Thus, this decision support system is expected to have the ability to provide advice or recommendations. shoes that suit customers' needs and preferences, helping them overcome the confusion in choosing among the various shoe models available in the market.